The Relevance of Improving the Efficiency of Labor Protection Issues in the Pharmaceutical Industry - Akromkulovna, Khojieva Shakhoza; Murtozaevich, Narziev Shovkiddin (European Journal of Life Safety and Stability (2660-9630), 2022)
The pharmaceutical industry, which is one of the main sectors of the country’s economy, currently has about 180 enterprises and organizations that employ about 34,000 people. Most workers in this sector work in potentially hazardous jobs. This article analyzes the causes of accidents occurring in the pharmaceutical industry. Also, the majority of accidents in the industry are severe, accounting for 33% of all accidents. The number of victims of accidents is also 65%. As a result of the study, measures were taken to prevent accidents in pharmacy organizations and recommendations were developed to improve working conditions.